Study guides

☆☆

Q: What is the answer for x2 plus 1 plus 3x4 equals 2?

Write your answer...

Submit

Still have questions?

Related questions

x6 + 3x4 - x2 - 3 = 0(x6 + 3x4) - (x2 + 3) = 0x4(x2 + 3) - (x2 + 3) = 0(x2 + 3)(x4 - 1) = 0(x2 + 3)[(x2)2 - 12] = 0(x2 + 3)(x2 + 1)(x2 - 1) = 0(x2 + 3)(x2 + 1)(x + 1)(x - 1) = 0x2 + 3 = 0 or x2 + 1 = 0 or x + 1 = 0 or x - 1 = 0x2 + 3 = 0x2 = -3x = ±√-3 = ±i√3 ≈ ±1.7ix2 + 1 = 0x2 = -1x = ±√-1 = ±i√1 ≈ ±ix + 1 = 0x = -1x - 1 = 0x = 1The solutions are x = ±1, ±i, ±1.7i.

(3x4 + 2x3 - x2 - x - 6)/(x2 + 1)= 3x2 + 2x - 4 + (-3x - 2)/(x2 + 1)= 3x2 + 2x - 4 - (3x + 2)/(x2 + 1)where the quotient is 3x2 + 2x - 4 and the remainder is -(3x + 2).

This is an expression and you do not solve an expression, but you can factor this one.X2 + 3X4X2(1 + 3X2)========

x(x + 1)

x^5+2x^4+4x^2+2x-3

x2 + x2 + x2 = (1 + 1 + 1)x2 = 3x2

The vertex is at (-1,0).

(xn+2-1)/(x2-1)

x2 + 2x -6 = 0 x2 + 2x + 1 = 7 (x + 1)2 = 7 x = -1 ± √7

No.

The four solution values of x of 3x4 + 7x3 + 4x2 = 0 are: x = -11/3, -1, 0 (repeated) 3x4 + 7x3 + 4x2 = 0 ⇒ x2(3x2 + 7x + 4) = 0 ⇒ x2(3x + 4)(x + 1) = 0 ⇒ x2 = 0 → x = 0 (repeated) or (3x + 4) = 0 → x = -4/3 = -11/3 or (x + 1) = 0 → x = -1

No, that's a parabola.

People also asked